Effects of decarburization on the wear resistance and damage mechanisms of rail steels subject to contact fatigue - Zhao, X.J.; Guo, J.; Wang, H.Y.; Wen, Z.F.; Liu, Q.Y.; Zhao, G.T.; Wang, W.J. (Wear, 2016)
Decarburization can remain on the surfaces of rail head steels and affect their wear and damage processes. The current research explored the influence of a decarburized layer on wear resistance and damage behavior of rail materials using a rolling–sliding wear testing machine. A decarburized layer decreases the hardness and wear resistance of rail steels, and the wear rate of a decarburized rail is over twice that of the same steel without decarburization. Multi-layer peeling appears on rail rollers without decarburization, but a decarburized layer changes the damage mechanism of the rail steel. With an increase in the depth of decarburization, the damage of rail roller turns from major spalling to pitting and peeling. In addition, surface fatigue cracks become more serious as depth increases. By contrast, shallow decarburization has little effect on rolling contact fatigue (RCF) of the rail material. Only when the depth of the decarburization exceeds a certain thickness (i.e., about 0.5mm based on the present results), RCF damage sharply worsens as decarburization depth increases. Furthermore, adhesive wear features are obvious on the rail roller only when a decarburized zone remains at the wear surface. •Wear rate of decarburized rail is over 2 times than that of normal rail.•The decarburized layer transforms the damage mechanism of rail material.•There are different crack growth mechanisms on the normal and decarburized rail.•Large depth of decarburization sharply increases growth rate of rail cracks.